A negative structure for a solid-state electrolyte lithium metal battery
Patent Information
- Application Number
- CN202211209512.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-09-30
AI Technical Summary
[0006]采用这种负极结构的缺点在于,电池长时间运行时,熔盐界面层容易流失,导致负极集流体和陶瓷电解质之间的锂离子传导不畅,界面电阻增大,且没有熔盐界面层阻隔时,金属锂直接接触陶瓷电解质,会腐蚀陶瓷电解质,影响电池循环寿命
[0041]其技术效果是:这种负极结构能够在负极集流体与陶瓷电解质之间构筑持久稳定的熔盐界面层,在电池长时间运行过程中维持低界面电阻,并有效减缓熔融金属锂对陶瓷电解质的腐蚀,提升电池循环稳定性和循环寿命。
Smart Images

Figure CN117810562B_ABST
Abstract
Description
Technical Field
[0001] This invention patent relates to a molten lithium metal battery anode structure in the field of chemical energy storage. Background Technology
[0002] Molten lithium metal batteries, developed in recent years, are expected to be applied in large-scale grid energy storage, backup power, and power batteries for large electric vehicles due to their high safety, high energy density, and low cost.
[0003] CN202210022945.8 discloses a high-temperature molten lithium-iodine battery based on garnet solid electrolyte, including garnet solid electrolyte, positive electrode material and negative electrode material. It uses a U-shaped garnet ceramic electrolyte tube as solid electrolyte, the inside of the U-shaped tube is filled with eutectic iodide as positive electrode, the outside of the U-shaped tube is filled with lithium metal between the stainless steel shell as negative electrode, and a graphite rod is used as current collector.
[0004] CN201710244878.3 discloses a double-layer negative electrode current collector for liquid metal batteries, which includes an electrode rod, a lithium-impregnated foam alloy A, and a lithium-free foam alloy B. The foam alloy A and foam alloy B are coaxially sleeved on the bottom of the electrode rod from top to bottom. The foam alloy A and foam alloy B are fixed to the bottom of the electrode rod by a nut set on the upper part of the foam alloy A and a nut in the groove at the bottom of the foam alloy B. The nut, foam alloy A, and foam alloy B are all tightly fitted together.
[0005] The main structure of the negative electrode current collector in the known molten lithium metal battery consists of a stainless steel mesh negative electrode current collector closely attached to the inner wall of the lithium-ion electrolyte ceramic tube and a molten salt interface layer immersed between the inner wall of the ceramic electrolyte tube and the stainless steel mesh.
[0006] The disadvantage of this negative electrode structure is that the molten salt interface layer is prone to loss during long-term battery operation, which leads to poor lithium-ion conduction between the negative electrode current collector and the ceramic electrolyte, increases the interface resistance, and when there is no molten salt interface layer to block it, the metallic lithium directly contacts the ceramic electrolyte, which will corrode the ceramic electrolyte and affect the battery cycle life. Summary of the Invention
[0007] The purpose of this invention is to overcome the shortcomings of the prior art and provide a novel negative electrode structure for molten lithium metal batteries. This structure can effectively suppress the loss of the molten salt interface layer between the lithium-ion ceramic electrolyte and the negative electrode current collector, thereby maintaining a low interface resistance and protecting the ceramic electrolyte, and improving battery performance and cycle life.
[0008] Based on existing technologies, the inventors have optimized the process by placing a porous adsorption layer that adsorbs molten salt from the negative electrode between the ceramic electrolyte and the current collector, thereby suppressing molten salt loss and constructing a durable and stable molten salt interface layer between the ceramic electrolyte and the current collector.
[0009] One technical solution to achieve the above objective is: a negative electrode structure for a molten lithium metal battery, comprising a material for a negative electrode post, a material and structure for a negative electrode current collector, a material and structure for a negative electrode porous adsorption layer, and a negative electrode molten salt material, wherein the negative electrode porous adsorption layer adsorbs the negative electrode molten salt material and is placed between the negative electrode current collector and the inner wall of the ceramic electrolyte tube, and is in close contact with both.
[0010] Furthermore, the mass of the negative electrode molten salt adsorbed by the negative electrode porous adsorption layer is 0.1-100 times, preferably 1-50 times, or 2-20 times the mass of the negative electrode porous adsorption layer, and the negative electrode current collector is connected to the negative electrode post.
[0011] Furthermore, the negative electrode post uses a conductive rod, including but not limited to stainless steel rods, copper rods, graphite rods, etc.
[0012] Furthermore, the negative electrode current collector is a metal mesh, including but not limited to stainless steel mesh, galvanized stainless steel mesh, copper-plated stainless steel mesh, brass-plated stainless steel mesh, tungsten mesh, nickel mesh, etc.
[0013] Furthermore, the porous adsorption layer of the negative electrode is a material with a porous structure. This porous adsorption layer is characterized by its stability to molten lithium metal, good thermal stability, and wettability with the molten salt of the negative electrode. Its porosity is 20%-95%, and its thickness is 0.05-3 mm. Materials include, but are not limited to, carbon felt, carbon cloth, copper foam, nickel foam, iron foam, iron-nickel foam, porous magnesium oxide ceramic, and porous lithium aluminate ceramic. The porous adsorption layer adsorbs the molten salt of the negative electrode and adheres closely to the inner wall of the lithium-ion ceramic electrolyte.
[0014] Furthermore, the negative electrode molten salt is a single salt or a mixture of several salts that is stable to molten lithium metal, has a melting point below 400°C, and contains lithium ions, thus enabling it to conduct lithium ions. These salts include, but are not limited to, mixed salts such as LiI-CsI, LiCl-KCl, LiBr-KBr, LiF-LiBr-LiI, LiCl-KCl-CsCl, and LiBr-KBr-CsBr.
[0015] This invention also provides a method for preparing a negative electrode structure for a molten lithium metal battery, comprising:
[0016] (1) Fabricate the negative electrode current collector according to the size and height of the ceramic electrolyte tube.
[0017] (2) Based on the size of the negative electrode current collector, use a suitable size of porous adsorption layer material to cover the negative electrode current collector mesh cylinder around its perimeter. After covering the negative electrode current collector with the porous adsorption layer, place the entire assembly into the ceramic electrolyte tube.
[0018] (3) Add negative electrode molten salt into the ceramic electrolyte tube and allow the molten salt to be uniformly adsorbed by the negative electrode porous adsorption layer at high temperature.
[0019] (4) After adsorbing the negative electrode molten salt, the negative electrode current collector is fixedly connected to the negative electrode post to complete the fabrication of the negative electrode structure.
[0020] Furthermore, the negative electrode current collector is made of woven metal wires in the shape of a mesh tube.
[0021] Furthermore, the mass of the negative electrode molten salt adsorbed by the negative electrode porous adsorption layer is 0.1-100 times, preferably 1-50 times, or 2-20 times the mass of the negative electrode porous adsorption layer, and the negative electrode current collector is connected to the negative electrode post.
[0022] Furthermore, the negative electrode post uses a conductive rod, including but not limited to stainless steel rods, copper rods, graphite rods, etc.
[0023] Furthermore, the negative electrode current collector is a metal mesh, including but not limited to stainless steel mesh, galvanized stainless steel mesh, copper-plated stainless steel mesh, brass-plated stainless steel mesh, tungsten mesh, nickel mesh, etc.
[0024] Furthermore, the porous adsorption layer of the negative electrode is a material with a porous structure. This porous adsorption layer is characterized by its stability to molten lithium metal, good thermal stability, and wettability with the molten salt of the negative electrode. Its porosity is 20%-95%, and its thickness is 0.05-3 mm. Materials include, but are not limited to, carbon felt, carbon cloth, copper foam, nickel foam, iron foam, iron-nickel foam, porous magnesium oxide ceramic, and porous lithium aluminate ceramic. The porous adsorption layer adsorbs the molten salt of the negative electrode and adheres closely to the inner wall of the lithium-ion ceramic electrolyte.
[0025] Furthermore, the negative electrode molten salt is a single salt or a mixture of several salts that is stable to molten lithium metal, has a melting point below 400°C, and contains lithium ions, thus enabling it to conduct lithium ions. These salts include, but are not limited to, mixed salts such as LiI-CsI, LiCl-KCl, LiBr-KBr, LiF-LiBr-LiI, LiCl-KCl-CsCl, and LiBr-KBr-CsBr.
[0026] This invention also provides another method for preparing a negative electrode structure for a molten lithium metal battery, comprising:
[0027] (1) Select a suitable cylinder based on the inner diameter and height of the ceramic electrolyte tube, and place the cylinder inside the ceramic electrolyte to form a uniform and regular gap between it and the inner wall of the ceramic electrolyte.
[0028] (2) The porous ceramic powder particles are fully filled with the gaps and sintered at high temperature. After molding, the cylinder is removed and the molded porous ceramic becomes the negative electrode porous adsorption layer.
[0029] (3) Based on the size of the ceramic electrolyte tube and the porous adsorption layer of the negative electrode, select a negative electrode current collector of appropriate size, process it into a cylindrical shape and insert it into the negative electrode chamber, closely adhering to the inner wall of the porous ceramic.
[0030] (4) Add negative electrode molten salt into the ceramic electrolyte tube and allow the molten salt to be uniformly adsorbed by the porous magnesium oxide ceramic layer at high temperature.
[0031] (5) After adsorbing the negative electrode molten salt, the negative electrode current collector is fixedly connected to the electrode post, thus completing the fabrication of the negative electrode structure.
[0032] Furthermore, the mass of the negative electrode molten salt is 0.1-100 times, preferably 1-50 times, or 2-20 times, the mass of the negative electrode porous adsorption layer, and the negative electrode current collector is connected to the negative electrode post.
[0033] Furthermore, the negative electrode post uses a conductive rod, including but not limited to stainless steel rods, copper rods, graphite rods, etc.
[0034] Furthermore, the negative electrode current collector is a metal mesh, including but not limited to stainless steel mesh, galvanized stainless steel mesh, copper-plated stainless steel mesh, brass-plated stainless steel mesh, tungsten mesh, nickel mesh, etc.
[0035] Furthermore, the porous adsorption layer of the negative electrode is a material with a porous structure. This porous adsorption layer is characterized by its stability to molten lithium metal, good thermal stability, and wettability with the molten salt of the negative electrode. Its porosity is 20%-95%, and its thickness is 0.05-3 mm. Materials include, but are not limited to, carbon felt, carbon cloth, copper foam, nickel foam, iron foam, iron-nickel foam, porous magnesium oxide ceramic, and porous lithium aluminate ceramic. The porous adsorption layer adsorbs the molten salt of the negative electrode and adheres closely to the inner wall of the lithium-ion ceramic electrolyte.
[0036] Furthermore, the negative electrode molten salt is a single salt or a mixture of several salts that is stable to molten lithium metal, has a melting point below 400°C, and contains lithium ions, thus enabling it to conduct lithium ions. These salts include, but are not limited to, mixed salts such as LiI-CsI, LiCl-KCl, LiBr-KBr, LiF-LiBr-LiI, LiCl-KCl-CsCl, and LiBr-KBr-CsBr.
[0037] The present invention also provides an application of a porous adsorption layer material for adsorbing molten salt material in a molten metal lithium battery, wherein the porous adsorption layer is placed between the negative electrode current collector and the inner wall of the ceramic electrolyte tube in the negative electrode structure.
[0038] Furthermore, the negative electrode molten salt is a single salt or a mixture of several salts that is stable to molten lithium metal, has a melting point below 400°C, and contains lithium ions, thus enabling it to conduct lithium ions. These salts include, but are not limited to, mixed salts such as LiI-CsI, LiCl-KCl, LiBr-KBr, LiF-LiBr-LiI, LiCl-KCl-CsCl, and LiBr-KBr-CsBr.
[0039] Furthermore, the negative electrode structure is the aforementioned negative electrode structure, or the negative electrode structure prepared by the aforementioned preparation method.
[0040] The technical solution of the molten lithium metal battery negative electrode structure of the present invention includes the material of the negative electrode post, the material and structure of the negative electrode current collector, the material and structure of the negative electrode porous adsorption layer, and the material including negative electrode molten salt. The mass of the negative electrode molten salt adsorbed by the negative electrode porous adsorption layer is 0.1-100 times the mass of the negative electrode porous adsorption layer.
[0041] The technical effect is that this negative electrode structure can build a durable and stable molten salt interface layer between the negative electrode current collector and the ceramic electrolyte, maintain a low interface resistance during long-term battery operation, and effectively slow down the corrosion of the ceramic electrolyte by molten lithium metal, thereby improving the battery's cycle stability and cycle life. Attached Figure Description
[0042] Figure 1 This is a schematic diagram of the structure of a molten lithium metal battery negative electrode according to the present invention.
[0043] Figure 2 The charge-discharge curves of a molten lithium symmetric battery assembled using the technical solution proposed in this invention are shown.
[0044] Figure 3 Charge-discharge curves of a molten lithium symmetric battery assembled without a porous adsorption layer structure.
[0045] Please see Figure 1 The negative electrode structure of the molten lithium metal battery of this invention patent consists of, from the outside to the inside, a lithium-ion ceramic electrolyte tube 2; a porous adsorption layer 3; a molten salt 4; a current collector 1; and a negative electrode post 5. Detailed Implementation
[0046] To better understand the technical solution of this invention patent, detailed descriptions are provided below through specific embodiments and in conjunction with the accompanying drawings:
[0047] Example 1:
[0048] This embodiment describes a process implementation method for a porous adsorption layer material with curling deformation properties. Porous adsorption layers with curling deformation properties include, but are not limited to, materials with porous structures such as carbon felt, carbon cloth, copper foam, nickel foam, iron foam, and iron-nickel foam.
[0049] Taking the specific implementation process of carbon felt as an example:
[0050] (1) The negative electrode current collector 1 should be made according to the inner diameter and height of the ceramic electrolyte tube 2. The negative electrode current collector is made of metal wire braided into a mesh tube shape.
[0051] (2) Based on the outer diameter and height of the negative electrode current collector 1, use a suitable size of negative electrode porous adsorption layer material to cover the current collector mesh cylinder around the perimeter. After the negative electrode porous adsorption layer 3 covers the negative electrode current collector 1, the whole thing is placed into the ceramic electrolyte tube 2.
[0052] (3) Add LiBr-KBr-CsBr (mass ratio of 39.08%:18.17%:42.75%) negative electrode molten salt 4 into the ceramic electrolyte tube. The mass of the molten salt is 20 times the mass of the carbon felt. At high temperature, the molten salt is uniformly adsorbed by the porous adsorption layer 3 of the negative electrode.
[0053] (4) After adsorbing the negative electrode molten salt, the negative electrode current collector 1 is fixedly connected to the electrode post 5, thus completing the fabrication of the negative electrode structure.
[0054] (5) Assemble a lithium-to-lithium battery with the negative electrode structure and perform charge-discharge tests on it using an electrochemical testing system.
[0055] Figure 2 The diagram shows the charge-discharge curves of a molten lithium symmetric battery assembled using the technical solution proposed in this invention. After being left to stand for 24 hours, the battery can still charge and discharge stably, with a stable operating time of 20,000 minutes and an average coulombic efficiency of about 95%.
[0056] Experimental comparisons revealed that the molten lithium symmetric battery assembled without the porous adsorption layer structure (the rest of the structure was consistent with Example 1) performed better than that assembled in Example 1. Figure 3 As shown, after standing for 24 hours, the molten salt interface layer is lost, resulting in high interface resistance and preventing normal charging and discharging.
[0057] The negative electrode current collector structure of this invention can make close contact with the ceramic electrolyte tube, increase the contact area between the porous adsorption layer 3 and the molten lithium salt 4 adsorbed on the porous adsorption layer and the inner wall of the ceramic electrolyte, and maintain a stable contact area, thereby making the lithium ion pathway more uniform and stable; it can construct a durable and effective negative electrode molten salt interface layer between the lithium ion ceramic electrolyte and the negative electrode current collector, maintain a low interfacial lithium ion conduction resistance, and at the same time slow down the corrosion of the ceramic electrolyte by molten lithium metal, thereby improving the battery cycle stability.
[0058] Example 2:
[0059] In this embodiment, a process implementation method is described for a porous adsorption layer material with a negative electrode that is not easily curled or deformed. The porous adsorption layer with a negative electrode that is not easily curled or deformed includes, but is not limited to, porous magnesium oxide ceramics, porous lithium aluminate ceramics, and other materials with porous structures. Because their size cannot be adjusted, an in-situ sintering process is adopted.
[0060] Taking the specific implementation process of porous magnesium oxide ceramics as an example:
[0061] (1) Select a suitable stainless steel cylinder according to the inner diameter and height of the ceramic electrolyte tube 2, and place the cylinder inside the ceramic electrolyte so that a uniform and regular gap is formed between it and the inner wall of the ceramic electrolyte.
[0062] (2) The porous magnesium oxide ceramic powder particles are fully filled with the gaps and sintered at high temperature. After molding, the stainless steel cylinder is removed, and the molded porous magnesium oxide ceramic becomes the negative electrode porous adsorption layer.
[0063] (3) Based on the size of the ceramic electrolyte tube 2 and the porous adsorption layer 3 of the negative electrode, select a metal mesh of appropriate size, process it into a cylindrical shape, insert it into the negative electrode current collector 1, and attach it tightly to the inner wall of the porous magnesium oxide ceramic.
[0064] (4) Add LiI-CsI (mass ratio of 50%:50%) negative electrode molten salt 4 into the ceramic electrolyte tube 2. The mass of the molten salt is 1.2 times the mass of the porous magnesium oxide layer. At high temperature, the molten salt is uniformly adsorbed by the porous magnesium oxide ceramic layer.
[0065] (5) After adsorbing the negative electrode molten salt, the negative electrode current collector 1 is fixedly connected to the electrode post 5, thus completing the fabrication of the negative electrode structure.
[0066] The present invention discloses a negative electrode structure for solid electrolyte molten lithium metal batteries that can construct a durable and effective negative electrode molten salt interface layer between the lithium-ion ceramic electrolyte and the negative electrode current collector, maintain a low interfacial lithium-ion conduction resistance, and at the same time slow down the corrosion of the ceramic electrolyte by molten lithium metal, thereby improving the cycle stability of the battery.
[0067] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. It can be applied to various fields suitable for the present invention. Other modifications can be readily made by those skilled in the art. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and examples shown and described herein.
Claims
1. A negative electrode structure for a molten lithium metal battery, comprising a negative electrode post, a negative electrode current collector, a porous negative electrode adsorption layer, and a negative electrode molten salt, wherein the porous negative electrode adsorption layer adsorbs the negative electrode molten salt and is placed between the negative electrode current collector and the inner wall of a ceramic electrolyte tube, and is in close contact with both; the negative electrode current collector is connected to the negative electrode post, and the negative electrode current collector is a metal mesh. in, The porous adsorption layer of the negative electrode has a porosity of 20%-95% and a thickness of 0.05-3mm, including carbon felt, carbon cloth, copper foam, nickel foam, iron foam, iron-nickel foam, porous magnesium oxide ceramic, or porous lithium aluminate ceramic. The negative electrode molten salt includes LiI-CsI, LiCl-KCl, LiBr-KBr, LiF-LiBr-LiI, LiCl-KCl-CsCl, or a mixed salt of LiBr-KBr-CsBr; The mass of the negative electrode molten salt adsorbed by the negative electrode porous adsorption layer is 0.1-100 times the mass of the negative electrode porous adsorption layer.
2. A method for preparing the negative electrode structure of a molten lithium metal battery according to claim 1, comprising: (1) Fabricate the negative electrode current collector according to the inner diameter and height of the ceramic electrolyte tube. (2) Based on the size of the negative electrode current collector, use a suitable size of porous adsorption layer material to cover the negative electrode current collector mesh cylinder around its perimeter. After covering the negative electrode current collector with the porous adsorption layer, place the entire assembly into the ceramic electrolyte tube. (3) Add negative electrode molten salt into the ceramic electrolyte tube, and at high temperature, allow the molten salt to be uniformly adsorbed by the porous adsorption layer of the negative electrode. (4) After adsorbing the negative electrode molten salt, the negative electrode current collector is fixedly connected to the negative electrode post to complete the fabrication of the negative electrode structure.
3. A method for preparing the negative electrode structure of a molten lithium metal battery according to claim 1, comprising: (1) Select a suitable cylinder according to the inner diameter and height of the ceramic electrolyte tube, and place the cylinder inside the ceramic electrolyte to form a uniform and regular gap between it and the inner wall of the ceramic electrolyte. (2) The porous ceramic powder particles are fully filled with the gaps and sintered at high temperature. After molding, the cylinder is removed and the molded porous ceramic becomes the negative electrode porous adsorption layer. (3) Based on the size of the ceramic electrolyte tube and the porous adsorption layer of the negative electrode, select a negative electrode current collector of appropriate size, process it into a cylindrical shape and insert it into the negative electrode chamber, closely adhering to the inner wall of the porous ceramic. (4) Add negative electrode molten salt into the ceramic electrolyte tube and allow the molten salt to be uniformly adsorbed by the porous adsorption layer of the negative electrode at high temperature. (5) After the negative electrode molten salt is adsorbed, the negative electrode current collector is fixedly connected to the electrode post, thus completing the fabrication of the negative electrode structure.
4. The method for preparing the negative electrode structure according to claim 2 or 3, characterized in that, The mass of the negative electrode molten salt adsorbed by the negative electrode porous adsorption layer is 1-50 times the mass of the negative electrode porous adsorption layer.
5. The method for preparing the negative electrode structure according to claim 2 or 3, characterized in that, The mass of the negative electrode molten salt adsorbed by the negative electrode porous adsorption layer is 2-20 times the mass of the negative electrode porous adsorption layer.
6. A negative electrode structure prepared by the preparation method according to any one of claims 2-5.
7. The application of the porous adsorption layer for negative electrodes as defined in any one of claims 1-6 in a molten metal lithium battery, wherein the porous adsorption layer for negative electrodes is disposed between the negative electrode current collector of the negative electrode structure and the inner wall of the ceramic electrolyte tube.
Citation Information
Patent Citations
A bilayer negative electrode current collector for liquid metal batteries and its preparation method
CN106972174B
High-temperature melting lithium-iodine battery based on garnet solid electrolyte
CN114335758A
Composite negative-pole tube for battery
CN106711465A
Composite lithium metal negative electrode, preparation method and lithium ion battery
CN109713224A